Entrepreneurship : Krep-Krep Enterprise / Muhammad Firdaus Zabidi ... [et al.] - Zabidi, Muhammad Firdaus; Zakaria, Mohd Nur Azry; Ali Mohtar, Mohd Syazani; Zainal, Ahmad Farid; Khamarul Zaman, Mohd Faris Faruqi (2009)
KREP-KREP ENTERPRISE is the company that will establish by five members which is consists of Muhammad Firdaus b Zabidi, Mohd Nur Azry b Zakaria, Mohd Syazani b Ali Mohtar, Ahmad Farid b Zainal, Muhammad Faris Faruqi b Kamarul Zaman. We named our company as KREP-KREP which came from the word “kerepek” in malay. As you can expect from our company name, we are making business of supplying and selling three kind of chips that is potato, banana and yam.